Akuntabilitas Dan Transparansi Lembaga Pengelola Zakat Melalui Zakat Core Principles Dan PSAK 109 - Zahara, Hanifatus Syaidah; Meisya Zahra; Arini Prawita; Silvia Zahra Syahidah; Elis Nurhasanah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine how the implementation of the Basic Principles of Zakat and PSAK 109 can create accountability and transparency in zakat management institutions. Accountability and transparency are important issues in zakat management governance because they are related to public trust, zakat management agencies in order to improve accountability and transparency must prepare financial reports in accordance with applicable standards, namely PSAK accounting for zakat, infaq and sadaqah 109. In the governance of zakat, the standard of zakat management is introduced, namely the Zakat Core Principle (ZCP). This research method is qualitative research using library research methods, by collecting data related to the object of research in the form of books, manuscripts, periodicals or magazines, or collecting data in the form of literature, to solve a fundamental problem based on critical analysis and analysis of relevant in-depth knowledge about library materials. The findings of this study indicate that the implementation of Zakat Core Principles (ZCP) and PSAK 109 Accounting for Zakat can support the accountability and transparency of zakat management bodies. Among the zakat core principles, there are 6 principles related to zakat management, which reflect accountability and transparency.